Maxim of Politeness in â€œSpies In Disguiseâ€ Movie - Sakti, Anak Agung Bagus Wahana; Aryani, I Gusti Agung Istri; Putra, I Komang Sumaryana (LITERA : Jurnal Bahasa Dan Sastra, 2023)
This study entitled Maxim of Politeness in â€œSpies In Disguiseâ€ Movie. This study focusses on the find out the types of politeness maxim applied by the characterâ€™s conversation in the â€œSpies In Disguiseâ€ movie. The aim is to identify the type of maxim used in the conversation that occurs with the characters in the movie "Spies In Disguise". Documentation approach and note-taking strategy is used to collected the data and the data was qualitatively analyzed. The theory proposed by Leech (1983) is used to analyse what type of politeness maxims used are applied in the movie.